Final answer:
To solve the algebraic equation '3(2x+6) = 60', we distribute the 3 inside the parentheses, subtract 18 from both sides, and then divide by 6 to isolate x, leading to the solution x = 7.
Step-by-step explanation:
To prove that 3(2x+6) = 60, we need to show that both sides of the equation are equal.
First, start by distributing the 3 to the terms inside the parentheses:
3 * 2x + 3 * 6 = 60
This simplifies to:
6x + 18 = 60
Next, subtract 18 from both sides of the equation:
6x = 42
Finally, divide both sides of the equation by 6 to solve for x:
x = 7